Hindu philosophy : an exposition of the system of Kapila - Davies, John, d. 1890 (Trübner's oriental series., 1981)
Chiefly exposition of Īśvarakrṣṇa's Sāṅkhyakārikā, verse work on Sankhya philosophy.